Comparative study between S-N and fracture mechanics approach on reliability assessment of offshore wind turbine jacket foundations - Shittu, Abdulhakim Adeoye; Mehmanparast, Ali; Hart, Phil; Kolios, Athanasios (Elsevier, 2021)
This paper investigates from a structural reliability assessment (SRA) perspective the fatigue reliability using the S-N curve approach compared with the fracture mechanics (FM) approach for a typical welded offshore wind turbine (OWT) jacket support structure. A non-intrusive formulation was developed for an OWT jacket support structure in 50 m deep water, consisting of a sequence of steps. First, stochastic parametric 3D (three-dimensional) Finite Element Analysis (FEA) simulations are performed, taking into account stochastic variables such as wind loads, wave loads and soil properties using facilities within the software package ANSYS. Secondly, the FEA results are post-processed using an Artificial Neural Network (ANN) response surface modelling technique deriving the performance functions expressed in terms of stochastic variables. Finally, the First Order Reliability Method (FORM) is applied in calculating the reliability index values of components. The developed framework was applied to elucidate the fatigue damage process, including the small to long crack transition amongst other stages, for structural steels used for OWT jacket applications. The FM formulation investigated includes a crack growth formulation based on the bilinear crack growth law, considering both segments of the crack growth law as non-correlated and correlated in calculating the reliability index (RI). Sensitivity analysis results showed a strong dependence of the structure's reliability levels on the uncertainties of the crack growth law constants measured in terms of coefficient of variation (COV). Also investigated, was the reliability of the structure reassessed and updated in the presence of assumed structural health monitoring/ condition monitoring (SHM/CM) data. The results from the case study revealed that fracture reliability is highly sensitive to the initial crack size. It is recommended to apply the S-N curve method at the design stage while the FM approach applied towards the end of the design life as the structure approaches failure.
Keywords: Fatigue; Reliability index; Non-intrusive formulations; Crack growth; Offshore wind structures; Artificial neural network